Introduction to special issue about election reporting: Why journalism (still) matters. (August 2019) - Cushion, Stephen; Jackson, Daniel
This introduction unpacks the eight articles that make up this Journalism special issue about election reporting. Taken together, the articles ask: How has election reporting evolved over the last century across different media? Has the relationship between journalists and candidates changed in the digital age of campaigning? How do contemporary news values influence campaign coverage? Which voices – politicians, say or journalists – are most prominent? How far do citizens inform election coverage? How is public opinion articulated in the age of social media? Are sites such as Twitter developing new and distinctive election agendas? In what ways does social media interact with legacy media? How well have scholars researched and theorised election reporting cross-nationally? How can research agendas be enhanced? Overall, we argue this Special Issue demonstrates the continued strength of news media during election campaigns. This is in spite of social media platforms increasingly disrupting and recasting the agenda setting power of legacy media, not least by political parties and candidates who are relying more heavily on sites such as Facebook, Instagram and Twitter to campaign. But while debates in recent years have centred on the technological advances in political communication and the associated role of social media platforms during election campaigns (e.g. microtargeting voters, spreading disinformation/misinformation and allowing candidates to bypass media to campaign), our collection of studies signal the enduring influence professional journalists play in selecting and framing of news. Put more simply, how elections are reported still profoundly matters in spite of political parties' and candidates' more sophisticated use of digital campaigning.